Social isolation as a consequence of transitions in partner relationships: how formations and endings of partner relationships affect the risk of social disconnectedness - Eckhard, Jan (Journal of family research, 2021)
Objective: The study examines whether the risk of social isolation is affected by a union formation, marriage and by relationship endings. - Background: Social isolation is a broadly discussed social problem but little is known about how social isolation emerges. As regards the role of partner relationships, previous research has yielded mixed results on whether there are isolating effects of marriage, separations or widowhood. - Method: We use longitudinal data deriving from the German Socioeconomic Panel to analyse the impact of transitions in partner relationships on different manifestations of social isolation (disconnectedness from friends and relatives, non-participation in civic associations). Analyses on the impact of union formation and marriage are based on information on 11,359 persons. Analyses on the impact of relationship endings are based on information on 30,730 persons. - Results: Union formation and marriage are found to have little effect in terms of promoting social isolation. Endings of partner relationships, by contrast, entail an increased risk of being isolated at the same time from friendships, relatives and civil associations. - Conclusion: Taken together, the findings suggest that those who had limited their social interaction to the spouse or partner often fail to become re-integrated when the relationship had ended. It can be assumed that this is a common pathway into social isolation.
Publikationsdatum online: April 27, 2020
Gesehen am 22.08.2021